2019
DOI: 10.1002/gcc.22824
|View full text |Cite
|
Sign up to set email alerts
|

Discordant and heterogeneous clinically relevant genomic alterations in circulating tumor cells vs plasma DNA from men with metastatic castration resistant prostate cancer

Abstract: Circulating tumor cell (CTC) and cell-free (cf) DNA-based genomic alterations are increasingly being used for clinical decision-making in oncology. However, the concordance and discordance between paired CTC and cfDNA genomic profiles remain largely unknown. We performed comparative genomic hybridization (CGH) on CTCs and cfDNA, and low-pass whole genome sequencing (lpWGS) on cfDNA to characterize genomic alterations (CNA) and tumor content in two independent prospective studies of 93 men with mCRPC treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 48 publications
(209 reference statements)
2
15
1
Order By: Relevance
“…Gupta et al [48] presented results that are in line with the above statements. A paired comparison of genomic alterations between CTCs and cfDNA in metastatic castration-resistant prostate cancer, showed both concordance and disconcordance of certain alterations.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Gupta et al [48] presented results that are in line with the above statements. A paired comparison of genomic alterations between CTCs and cfDNA in metastatic castration-resistant prostate cancer, showed both concordance and disconcordance of certain alterations.…”
Section: Discussionsupporting
confidence: 66%
“…A paired comparison of genomic alterations between CTCs and cfDNA in metastatic castration-resistant prostate cancer, showed both concordance and disconcordance of certain alterations. The results enabled the prognosis of the clinical outcome for certain relations to be specified and proved that tumor heterogeneity is strictly linked to poor clinical outcomes [48].…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, unraveling the phenotypic and molecular pro le of CTCs provides key information about tumor biology and contributing to individualized precision treatment [37]. Nevertheless, the applicability of CTCs as a clinical biomarker has been challenged by their rarity and heterogeneity [38,39]. Numerous approaches [37,40,41] for detecting CTCs were proposed but are still not commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the issue of tissue heterogeneity remains, as analysis of needle biopsies does not always represent the whole tumor. Interestingly, liquid biopsy analysis of PTEN genomic status within circulating tumor cells (CTCs) is also being investigated as a quick, non-invasive strategy to identify patients with PTEN-deficient prostate cancer, with a view to inform treatment decisions [ 74 , 75 ]. For instance, a blood-based CTC PTEN FISH assay is being employed in a clinical trial exploring abiraterone in combination with PI3K/AKT inhibitors in patients with CRPC (NCT01485861) [ 74 ].…”
Section: Pten Status As a Predictive Biomarker For Prostate Cancermentioning
confidence: 99%
“…For instance, a blood-based CTC PTEN FISH assay is being employed in a clinical trial exploring abiraterone in combination with PI3K/AKT inhibitors in patients with CRPC (NCT01485861) [ 74 ]. Importantly, PTEN loss in CTCs isolated from patients with mCRPC has been shown to significantly correlate with reduced survival in two independent studies [ 74 , 75 ], and several studies have revealed that PTEN loss can influence response to current therapies [ 34 , 35 , 76 , 77 , 78 , 79 ]. Indeed, a recent large phase II trial in breast cancer is already using CTC DNA analysis to match key driver mutations in CTCs, including PTEN inactivating mutations, to select personalized therapies for patients, such as AKT-targeted therapy for PTEN-deficient patients [ 80 ].…”
Section: Pten Status As a Predictive Biomarker For Prostate Cancermentioning
confidence: 99%